A política de promoção da educação em direitos humanos no Sistema Municipal de Educação (SME) de Imperatriz/MA - DIAS JUNIOR, Clóvis Marques (2021)
The present dissertation has as its object of study the educational policies aimed at promoting human rights education and the general objective of the investigation is to analyze the policy of promoting human rights education in the Municipal Education System of Imperatriz/MA. The research follows a qualitative approach with the choice of a critical theory of reality based on historical-dialectical materialism with an epistemological basis, analyzing human rights, democracy and education as a policy, beyond its formal perspective. The work realizes a documental research on the Universal Declaration of Human Rights, the United Nations Declaration on Education and Training in Human Rights – UN Resolution n. 66/137, the National Plan for Education in Human Rights and the National Guidelines for Education in Human Rights - CNE/CP opinion n. 08/2012. The research shows that the normative instruments studied are arrows that indicate ways to implement human rights education in Brazil and the path, in this sense, still has a long way to go. The results count that the desirable school space should always be a citizen and democratic space, wich forms emancipated students, being of fundamental importance to approach human rights and democracy in the curriculum, in teaching, in transversal, transdisciplinary and extracurricular activities, in research, in the pedagogical project , in training professionals, in experiences and other forms of interaction with the community, all in a relationship of complexity. The conclusion verifies that in the Municipal Education System of Imperatriz, the Municipal Education Plan is the central instrument of the city's educational policy, and dealt with human rights as an objective, one goal and twenty strategic actions. Strategies are varied, including partnerships with social movements, universities and associations, government programs involving various municipal secretariats, work plans and projects within schools, curriculum adequacy, adoption and production of didactic-pedagogical materials focused on the theme of human rights and continuing training for educational professionals.